Improving English Language Students’ Oral Fluency through Youtube Non-Fiction Videos - Lydia Benmouhoub; Salima Maouche (The Journal of Studies in Language, Culture and Society)
Success in English language teaching and learning depends on the use of effective approaches, methods and strategies. Nevertheless, with the proliferation of new technological tools, a shift from teacher-centeredness to learner-based is necessary to promote a learning climate and reflective practice in higher education. In light of this, the present article probed the effect of using YouTube non-fiction videos as pedagogical tools on the development of English language students’ oral fluency. The aim is to change the traditional way of teaching the speaking skill, and move into a more dynamic and creative classroom atmosphere. To reach this purpose, the authors relied on a mixed-methods approach using four data collection tools, which consist of: teachers and students’ questionnaires, students’ evaluation checklist, unstructured interview as well as classroom observation.  The sample is composed of third year Literature and Civilisation students, teachers of oral expression and teachers of civilisation, at the department of English, University of Bejaia. The results showed students and teachers’ positive attitudes towards YouTube non-fiction videos in oral expression. In addition, they revealed that the use of YouTube videos as pedagogical tools implies three stages which are: pre-viewing, while-viewing, and after-viewing. Some insightful implications have been provided for further research.